Pharmacokinetics Study of 1-ethyl-6-fluoro-1, 4-dihydro-4-oxo-7-[4-[(4-amino N-acetyl) phenoxy carbonyl methyl]-1-piperazinyl]-3-quinoline carboxylic acidusing spectrophotometric method - Patil, Pravinbhai; Pagar, Khanderao; Patil, Pramod (Iranian Journal of Pharmaceutical Sciences, 2025)
A spectrophotometric method was derived to determine 1-ethyl-6-fluoro-1, 4-dihydro-4-oxo-7-[4-[(4-amino N-acetyl) phenoxy carbonyl methyl]-1-piperazinyl]-3-quinoline carboxylic acid (PPQC). This analytical method was simple, sensitive and low-cost. Based on forming of a chelate complex between PPQC and Fe(III), the developed method produced a yellow-colored complex that was detectable at 418 nm at room temperature. As per the International Conference on Harmonization guidelines, several analytical parameters for the suggested method were verified. With a correlation coefficient of 0.9998 (n=6) and a molar extinction coefficient of 1.2967 × 104 L mol-1 cm-1, the method was linear from 5 to 46 µg mL-1. The limit of detection (LOD) and limit of quantitation (LOQ) for the described method were 0.69 µg mL-1 and 2.09 µg mL-1, respectively. It was carefully examined and optimized how different parameters affected the chelate complex reaction. The recoveries of PPQC from spiked blood samples were 98.40-100.40%. The developed method’s coefficient of variation (CV) was less than 2.07%. The method validation was determined in accuracy, precision, absolute recovery, freeze–thaw stability, bench-top stability and long-term stability. After oral administration of PPQC to Wistar albino rats, the method’s analytical recovery, sensitivity, and accuracy were adequate to characterize the pharmacokinetics study. Thus, pharmacokinetics data for pre-clinical research have been obtained efficiently through the assay method.